Daylighting and energy performance of the combination of optical fiber based translucent concrete walls and windows. (15th May 2023) - Su, Xiaosong; Zhang, Ling; Liu, Zhongbing
Abstract: Optical fiber based translucent concrete (OFTC) is a kind of innovative building envelope for building energy efficiency. Prior studies indicated that both optical fibers and OFTC have angular transmittance that strongly depends on the angle of incidence, but most research on OFTC at the building level did not take this feature into account. This study focused on the annual daylighting and energy performance of the combination of OFTC walls with windows. The analysis was based on a cellular office room with an external OFTC wall and a window in Beijing, considering the influence of window-to-wall ratios, fiber volumetric ratios, optical fiber numerical aperture, and glazing types on building daylighting and energy performance. The results indicate that the combination of OFTC walls and windows can achieve the least net electricity use, which is about 32.07% and 5.36% lower than the optimal case with only OFTC walls, and that with the combination of conventional concrete walls and windows, respectively. The use of high numerical aperture optical fibers in OFTC can further contribute to building energy efficiency, but might increase the risk of daylight glare. However, the effects of OFTC walls on daylight glare are insignificant especially when the window-to-wall ratio is high. Highlights: Angular transmittance of optical fiber based translucent concrete was considered. Building energy simulation model of the translucent concrete was developed. Coupled effects of translucent concrete walls and windows on buildings were revealed. Building energy consumption was reduced by 5.36%∼32.07%.